The toxicity of brown algae (sargassum sp) extract to mice (mus muscullus) - Rahmat Wariz; Nur WR. Asfa; Abul Fauzi (Journal of Dentomaxillofacial Science, 2016)
Indonesian is a country with very large and overflow marine biological resources. Utilization of seaweed has been developed and become a source of revenue for Indonesian who live in coastal areas with high potential for seaweed.The demand of seaweed in the world increases as increasing in the use of seaweed for various purposeamong others in the fields of industry, food, textile, paper, paints, cosmetics, medical and pharmaceutical field. Alginate is one of materials that commonly used in the field of dentistry as printed materials to create study models. Materials in the field of dentistry must be biocompatible to the oral cavity tissues. The materials should be stable, safe, comfortable, and certainly doesn’t have a toxicity character to the oral cavity tissues and other tissues in human body. The purpose of this study is to know the toxicity of extract brown algaeSargassum sp given orally to mice.The research perform experimental laboratory research type withexperimental post-tes-only control group design. The reseach samples applyfemales white mice (Mus muscullus). Research samples divided into 5 groups of 5 female mices for each treatment group. Treatment group 1 was given 500mg/kgBW doses of Sargassum sp, group 2 was given 1000mg/KgBW doses of Sargassum sp, group 3 was given 1500mg/KgBW doses of Sargassum sp, group 4 were 2000mg/KgBW doses of Sargassum sp, and a control group was given only dose of Na CMC. The result of this study isdose in humans are converted into 2000mg/KgBW in mice, is a doses that doesn’t cause the death of whole animals. Based of acute toxicity category, the extracts of Sargassum sp that obtained from Punaga Takalar Regency, South Sulawesi includes in the mild toxic.